Donor leukocyte trafficking during human ex vivo lung perfusion. Issue 7 (18th April 2022) - Lee, Andy Chao Hsuan; Edobor, Arianna; Wigakumar, Thirushan; Lysandrou, Maria; Johnston, Laura K.; McMullen, Phillip; Mirle, Vikranth; Diaz, Ashley; Piech, Ryan; Rose, Rebecca; Jendrisak, Martin; di Sabato, Diego; et al.
Abstract: Background: Ex vivo lung perfusion (EVLP) is used to assess and preserve lungs prior to transplantation. However, its inherent immunomodulatory effects are not completely understood. We examine perfusate and tissue compartments to determine the change in immune cell composition in human lungs maintained on EVLP. Methods: Six human lungs unsuitable for transplantation underwent EVLP. Tissue and perfusate samples were obtained during cold storage and at 1‐, 3‐ and 6‐h during perfusion. Flow cytometry, immunohistochemistry, and bead‐based immunoassays were used to measure leukocyte composition and cytokines. Mean values between baseline and time points were compared by Student's t test. Results: During the 1st hour of perfusion, perfusate neutrophils increased (+22.2 ± 13.5%, p  < 0.05), monocytes decreased (−77.5 ± 8.6%, p  < 0.01) and NK cells decreased (−61.5 ± 22.6%, p  < 0.01) compared to cold storage. In contrast, tissue neutrophils decreased (−22.1 ± 12.2%, p  < 0.05) with no change in monocytes and NK cells. By 6 h, perfusate neutrophils, NK cells, and tissue neutrophils were similar to baseline. Perfusate monocytes remained decreased, while tissue monocytes remained unchanged. There was no significant change in B cells or T cell subsets. Pro‐inflammatory cytokines (IL‐1b, G‐CSF, IFN‐gamma, CXCL2, CXCL1 granzyme A, and granzyme B) and lymphocyte activating cytokines (IL‐2, IL‐4, IL‐6, IL‐8) increased during perfusion. Conclusions: Early mobilization of innate immune cells occurs in both perfusate and tissue compartments during EVLP, with neutrophils and NK cells returning to baseline and monocytes remaining depleted after 6 h. The immunomodulatory effect of EVLP may provide a therapeutic window to decrease the immunogenicity of lungs prior to transplantation.